Relationship between Green Entrepreneurial Orientation and Financial Literacy on SMES' Financial Performance - Ningsih, Ni Luh Anik Puspa; Darma, I Ketut; Dewi, Made Pratiwi; Karyati, Ni Kadek Tata; Mustika, Rhenasya Oktiani; Sarmawa, I Wayan Gde (Jurnal Economia, 2025)
The growth of tourism encourages the growth of the Culinary MSME sector in Bali. The culinary sector is very vulnerable to producing waste. On the other hand, SMEs are expected to be oriented towards the concept of green entrepreneurship to minimize waste. This study aims to analyze the influence of the implementation of green entrepreneurial orientation (GEO) and financial literacy on the performance of SMEs. The subject of this study is culinary SMEs in Bali with the distribution of questionnaires to 100 samples. The analysis techniques used are descriptive analysis and inferential analysis with Partial Least Squares. The results of this study show that financial literacy has a significant positive effect on GEO, but financial literacy has a non-significant effect on the performance of culinary SMEs in Bali and GEO has a significant positive impact on the performance of culinary SMEs in Bali.